The purchase of the Diabetic Healthy Food Basket in Cyprus results in cost savings: Is it affordable among the low-income population? - Chrysostomou, Stavri; Koutsampelas, Christos; Andreou, Sofia N.; Pittas, Charalampos (My University, 2020)
Objective: The main objective was to assess the cost, acceptability and affordability of the Cypriot Diabetic Healthy Food Basket (DHFB). Design: The development of DHFB was based on the Cypriot HFB with adjustments based on the nutritional guidelines for diabetes as developed by the American Diabetes Association (ADA) and information retrieved through the questionnaires. Two DHFB were constructed for adult women and adult men (±40 years) diagnosed with diabetes. Affordability was defined as the cost of DHFB as a percentage of the Guaranteed Minimum Income (GMI). Setting: Cyprus. Participants: 422 diabetic patients aged 18-87 years from different socioeconomic backgrounds. Results: DHFB consists of eight food categories, similar to Cypriot HFB, but different specific food items. The total monthly budget for a diabetic woman is about 15 % (25·68 Euros less) lower compared with HFB, and the relative percentage for a diabetic man is about 16 % (37·58 Euros less). The total monthly budget for a diabetic woman is about 30 % lower (60·32 Euros less) compared with that of a diabetic man. For low-income adults receiving GMI, the proportion of income that would need to be spent on DHFB ranges from around 30 to 42 % for women and men, respectively. Conclusions: The cost of DHFB is lower compared with HFB, meaning that nutritional treatment based on the practice guidelines for diabetes could be a cost-efficient therapy for these patients. DHFB is still not affordable among low-income persons.
Keywords: Affordability; Healthy Food Basket; Cyprus; Diabetes